1982
DOI: 10.1002/app.1982.070270823
|View full text |Cite
|
Sign up to set email alerts
|

Gas sorption and transport in poly(phenylene oxide) and comparisons with other glassy polymers

Abstract: SynopsisThe sorption and transport of several gases in poly(pheny1ene oxide) were measured at 35"C, and the results have been analyzed in terms of the dual sorption/mobility models which have been successfully employed for this purpose for other glassy polymers. Both the extent of sorption and rate of permeation of gases are quite large for poly(pheny1ene oxide) compared to other glassy polymers with rigid chain backbones. It is shown that the high extent of sorption is owing to the high glass transition tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1

Year Published

1999
1999
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(103 citation statements)
references
References 13 publications
6
94
1
Order By: Relevance
“…32,33 For a wide variety of low molar mass liquids 34 and rubbery polymers, 31 for which S ϭ k D at low pressure, the slope of a plot of log k D versus T c is 0.0074. Toi and Paul 35 demonstrated that penetrant k D values in glassy polymers determined from the dualmode sorption model exhibit the same dependence on penetrant condensability. The slope of the best-fit line to the PTMSP data in Figure 2 is 0.0078 Ϯ 0.0005.…”
Section: Solubilitymentioning
confidence: 91%
“…32,33 For a wide variety of low molar mass liquids 34 and rubbery polymers, 31 for which S ϭ k D at low pressure, the slope of a plot of log k D versus T c is 0.0074. Toi and Paul 35 demonstrated that penetrant k D values in glassy polymers determined from the dualmode sorption model exhibit the same dependence on penetrant condensability. The slope of the best-fit line to the PTMSP data in Figure 2 is 0.0078 Ϯ 0.0005.…”
Section: Solubilitymentioning
confidence: 91%
“…Polyimides, polycarbonate, polysulfone, polyarylate, and other polymeric structures exhibit an increasing CЈ H with increasing glass transition temperatures. 39,[41][42][43] This behavior can be explained by polymeric chain rigidity and the nonequilibrium nature of glassy polymers. Glass transition temperature increases often arise from increased polymeric chain rigidity.…”
Section: Dual Mode Analysismentioning
confidence: 94%
“…A good agreement is also noticed between the values measured in our work on PS membranes and those reported in the literature. 12 The variations of the permeabilities as a function of the thermoplastic content are shown in Figures 2 and 3 and they clearly demonstrate that these coefficients increase as the thermoplastic content increases in the blends. The same trend is observed concerning the diffusion coefficients (Tables II and III).…”
Section: Properties Of the Filmsmentioning
confidence: 93%
“…[7][8][9][10] PPE membranes are known to exhibit high gas permeate flux 11 combined with interesting mechanical properties and high thermal stability (T g ϭ 210°C). The second one, polystyrene (PS) has a lower permeability 12 than PPE (about fivefold lower) but higher by one order of magnitude than those of the epoxy/amine system. This thermoplastic is more brittle than PPE and its glass transition temperature is lower than for PPE (T g PS ϭ 100°C).…”
Section: Introductionmentioning
confidence: 99%